PCT commissioning under patient choice: implications for Bedford Hospital - Lang, Susan; Wainwright, Charles E. R.; Sehdev, Kamal (Cranfield University, 2004)
Primary Care Trusts (PCTs) are responsible for commissioning secondary care for their local population, thus when patient choice comes into effect in December 2005 they will play a key role in choice by defining the four or five providers offered to GPs and patients for elective surgery. A broader overview on commissioning can be found in Cranfield University's report 'A Review of Patient Choice in the NHS' but the purpose of this document is to explain changes to the commissioning process under choice and the effect these might have on trusts. The Healthcare Management Research Group of Cranfield Postgraduate Medical School has been working with Bedford Hospital NHS Trust to evaluate the possible implications of patient choice. During February and March 2004 a number of meetings were held with key NHS stakeholders, including Strategic Health Authorities (SHAs), Primary Care Trusts (PCTs) and General Practitioners (GPs) in Bedfordshire, Hertfordshire, Cambridgeshire, Huntingdonshire and Northamptonshire, and also the Department of Health in London. Conclusions from these interviews were supported by a literature review of academic papers, news articles, books, government guidelines and patient surveys. In particular, the process by which PCTs commission secondary care providers is assessed and the nine pilot schemes were evaluated. Department of Health guidelines have only been issued for choice at six months so most PCTs are concentrating on meeting the six month target and have not yet formulated a plan for choice at referral. A dominant theme that emerged was therefore one of uncertainty, hence PCTs' predictions for how they will run choice form the basis of this paper rather than definitive policies.